Filosofía del siglo xix. Una visión sanmarquina de la historia de la filosofía - Cruz Rodríguez, Matías (2023)
The key matter I attempt to bring into the light is how 19th-Century Philosophy was viewed back in the day, and how we look back at it. Using a thesis from San Marcos in the 19th Century about the philosophy of that time, and the most recent lesson plans of the 19th Century Philosophy course, I seek to demonstrate Metaphysics, Vitalism, and Human Studies will not fade away  even though Scientificism seeks overshadowing and discredit them. Employing the 1876 thesis by San Marcos alumni Serafín Filomeno, and the lesson plans by Professors Fernando Muñoz and José Carlos Ballón, I shall uncover how it was seen and how we see the Philosophy of that time in San Marcos University. My findings are something we are living in today, Human Studies will never fade away given the necessity they imply, something Scientificism shall never disprove with their non-human tools.